2022
DOI: 10.17576/ijphr.1201.2022.04
|View full text |Cite
|
Sign up to set email alerts
|

Physical Inactivity and Its Associated Factors among Adults in Malaysia: Findings from National Health and Morbidity Survey (NHMS) 2019

Abstract: Introduction: Physical inactivity has been identified as the fourth leading risk factor for worldwide mortality with major implications towards general health. Monitoring the level of physical inactivity may reduce the burden of non-communicable diseases (NCDs) and their risk factors. This study aims to determine the prevalence of physical inactivity and its associated factors among adults aged 18 years and above in Malaysia. Methodology: Data was obtained from the National Health and Morbidity Survey (NHMS) 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“…Our findings also noted that men are less likely to participate in sufficiently active and very active PA compared to women. This is in contrast with previous studies, which showed females were less active compared to males [ 18 , 22 , 58 , 73 ]. The reason for this could be because more women compared to men were involved in domestic-related PA, which accounts for the biggest PA domain in this population.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings also noted that men are less likely to participate in sufficiently active and very active PA compared to women. This is in contrast with previous studies, which showed females were less active compared to males [ 18 , 22 , 58 , 73 ]. The reason for this could be because more women compared to men were involved in domestic-related PA, which accounts for the biggest PA domain in this population.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous literature has reported the physical activity patterns and factors associated with physical activity [ 17 , 18 , 19 , 20 , 21 ]. Evidence from the National Health and Morbidity Survey (NHMS) 2019 showed that the prevalence of physical inactivity among adults in Malaysia was 24.6%; which is higher in comparison to other Asian countries such as China, India and Hong Kong [ 22 ]. This brings us to the subject of interest, which is to explore the patterns of physical activity among the Malaysian population based on the four IPAQ domains, which are work, active transportation, domestic and yard work, and leisure time and factors associated with physical activity levels.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity (PA) is a powerful and inexpensive tool to prevent any kinds of disease, promote social interactions, and increase an individuals’ health and well-being (World Health Organization & Noncommunicable Diseases and Mental Health, 2003). Despite the benefits and positive outcome on one’s health through PA, sedentary behavior is still commonly seen around the world (Chan et al, 2017; Hallal et al, 2012), especially in the urban area (Alias et al, 2022; Wattelez et al, 2021). Physical inactiveness or sedentary lifestyle has shown to be an utmost risk factor for mobility and is linked to certain health risk such as developing cardiovascular disease, obesity, Type 2 diabetes, feelings of anxiety, and depression (Croezen et al, 2009; Rosqvist et al, 2009; Win et al, 2011).…”
mentioning
confidence: 99%